Komunikasi Spasial Situs Sejarah untuk Menguatkan Penjenamaan Kota sebagai Kota Pusaka - Siregar, Mariana Rista Ananda; Jayawinangun, Roni (representamen, 2020)
AbstractThis article was written in order to describe the preservation of cultural spatial assets in support of one of the pillars of the city of Bogor, which imagines the city as a Heritage City. Based on the results of research on the image of the city of Bogor as a place (place branding), the city tourism often offers historical heritage from various times. The Bogor City Government seems to see the superiority of this heritage as an asset to increase their own local income. The qualitative data of this study were obtained from a review of archives and policy documents, reinforced by quantitative data collected through questionnaires to the Bogor community regarding the spatial heritage assets in their city. The results showed that through the form of primary communication in the form of landscape strategies, infrastructure, and cultural behavior, people feel well the stimuli of their city which can image their city as a Heritage City. This is supported by the implementation of policies contained in the Regional Medium Term Development Plan which includes the revitalization of historical sites, strengthening of footpaths around the Bogor Botanical Gardens, and holding various events based on Indonesian national culture.Keywords: spatial communication, place naming, city naming, heritage city